풋콩용 조숙 다수성 신품종 ‘상원’ - 고종민(Jong-Min Ko); 백인열(In-Youl Baek); 한원영(Won-Young Han); 김현태(Hyun-Tae Kim); 오기원(Ki-Won Oh); 신상욱(Sang-Ouk Shin); 박금룡(Keum-Yong Park); 하태정(Tae-Jung Ha); 신두철(Doo-Chull Shin); 정명근(Myung-Geun Chung); 강성택(Sung-Taek Kang); 윤홍태(Hong-Tae Yun); et al. (Korean journal of breeding, 2010)
풋콩용 신품종 ‘상원’은 1997년 황색 대립이고 극조숙인 큰 올콩을 모본으로 하고 일본에서 도입된 Oshimamidori가 교배된 조합이다. 1998년부터 2002년도에 걸쳐 F1 - F5세대를 계통육종법으로 전개하여 풋콩 특성이 유망하여 선발된 YS1309- 2B-4-1-1 계통으로 생산력검정시험에서 수확시기가 빠르고 도복에 강한 대립 풋콩 다수성 계통으로 유망하여 선발된 밀양154호이다. ‘상원’의 그 주요특성은 다음과 같다. 1. 유한신육형이며 ‘Sangwon’, a new cultivar for vegetable soybean, was developed from the cross between ‘Keunolkong’ and ‘Oshimamidori’, and was released at the National Institute of Crop Science (NICS) in 2007. The goal to develop a vegetable soybean cultivar with green pod, early maturity, large seed size, high yield, lodging tolerance, and resistance to disease such as soybean mosaic virus (SMV). ‘Sangwon’ has light green pod, early maturity, large seed, short plant height, and lodging tolerance. ‘Sangwon’ has determinate growth habit, white flower, gray pubescence, and oval leaf shape. The matured seeds have a yellow seed coat with light brown hilum, and a yellow cotyledon. ‘Sangwon’ has 5.8 cm fresh pod length, 13.2mm fresh pod width, 69.5 g seed weight per 100 green seeds, 44.0% green seed protein content, and 14.8% green seed oil content. At the regional yield trials (RYT) for vegetable soybean from 2005 to 2007, ‘Sangwon’ shows strong resistance to soybean mosaic virus (SMV) and tolerance to lodging in fields. Fresh pods of ‘Sangwon’ were harvested at the beginning of August. In the same tests, fresh pod of ‘Sangwon’ (10.39ton/ha) yielded 5% higher than ‘Hwaeomputkong’ (9.90ton/ha).